MEKANISME PEMINDAHAN TAHANAN DI LAPAS WANITA DEWASA DI LAPAS KELAS II B KUPANG - Samara, Finsensius; Bani, Ferdinandus; Tasya Oeleu, Theofilla; G.W. Moa, Louisiano; A R. Yazakur, Patrick; Thithania Katoda, Ignechya (Gapenas Publisher, 2024)
The mechanism for transferring detainees at the Kupang Class IIB Adult Women's Correctional Institution (Lapas) is a process that aims to ensure the smooth implementation of the correctional system in accordance with applicable regulations. Prisoner transfers are carried out based on various considerations, such as prison capacity exceeding capacity, the need for special guidance, security factors, or certain legal situations. This process involves several important stages, starting from submitting an application, administrative and legal review and evaluation, to carrying out transfers which are carried out under strict supervision to ensure the security and safety of detainees. This mechanism is regulated by Law Number 12 of 1995 concerning Corrections and a number of other technical regulations, which emphasize the importance of protecting human rights and transparency in implementation. The challenges faced in this process include limited transportation facilities, coordination between agencies, and the geographical conditions of the Kupang region. Thus, good cooperation is needed between prison officers, police, prosecutors, and other related parties to ensure that the transfer of prisoners is effective, according to procedures, and oriented towards prisoner development.